Sources of information and perception of rural consumer - S, Balusamy; S, Vanitha (Journal of Management and Science, 2012)
Marketing plays a pivotal role in the growth and development of a country.It significantly contributes to income generation and employment. Efficient marketing strategy enables the marketer to provide right product, to right person and at the right time.Indian rural market is much larger than that of the urban market in terms of population,number of households and by way of geographic dispersal. Increased income level among rural households, improved infrastructure and favorable government policies offer a huge potential for rural marketing. As a result, manufacturers from India as well as abroad have diversified their attention towards rural segment to tap the hitherto untapped potential. Four billion people worldwide live in rural areas while in India 74 per cent of the population reside in rural areas, spreading over 3.2 million sq. km. in about 6,38,365 villages. Rural India is characterized by half a dozen religions, 33 languages, 1,650 dialects, and diversity in castes, sub-castes, tribes, culture, and subculture.